A fabrication of stable lithium metal anodes using HF scavenging films. Issue 19 (17th February 2023) - Cho, Sungjin; Son, Hye Bin; Lee, Sangyeop; Park, Soojin
Abstract : A stable lithium metal anode is fabricated by an electrodeposition process using a functional lithiophilic thin film polymer that provides numerous fluorine sources on the surface of the electrode and induces uniform lithium electrodeposition. Abstract : A stable lithium metal anode was fabricated using a functional lithiophilic thin film polymer. The functional film captures HF impurities in the electrolyte and provides a fluorine-rich surface. In addition, the lithiophilic properties and in situ formed stable solid-electrolyte-interphase layer induced uniform lithium electrodeposition and exhibited outstanding cell performance in both liquid and solid electrolytes.